From Struggle To Strategy: Home Isolation During The Sars-COV-2 Pandemic In Meruyung, Depok, Indonesia - Adzkia, Qonita; Kusumaratna, Rina K; Wahyuningsih, Sri (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2025)
The Indonesian government implemented various health procedures, including home isolation, to mitigate SARS-CoV-2 transmission. Despite these efforts, understanding public readiness for self-isolation is crucial. This study aimed to assess self-awareness and preparedness for home isolation during the initial phase of the COVID-19 pandemic (January-April 2020). Employing an analytical cross-sectional design, data were collected from 1169 participants (household heads, spouses, and elderly members ≥60 years) in 11 sub-districts of Limo Depok, West Java, Indonesia, using a validated scoring questionnaire on internal and external perceptions of home isolation. Descriptive analysis and Fisher's Exact test (p<0.05) were performed. Findings revealed a predominant female participation (66% aged ≥60 years), with case categories comprising 3% suspicious, 3.4% travelers, and 93.7% non-confirmation cases; 32% had comorbidities. A critical external factor was high population density, with only 19% of residential locations meeting excellent standards. Strikingly, only 20.5% of participants expressed willingness to practice home isolation. This study underscores a significant gap in the public's willingness and environmental suitability for effective home isolation. Raising awareness and empowering families to independently curb transmission are crucial. Lessons from local COVID-19 cases emphasize the vital role of collaborative management and network development among local stakeholders to enhance pandemic response strategies.